Direct observation and modeling of growth-induced stacking fault in chromium-rich γ-M23C6 carbides. (15th March 2020) - Souissi, M.; Sluiter, M.H.F.; Matsunaga, T.; Tabuchi, M.; Mills, M.J.; Sahara, R.
Abstract: γ-M23 C6 carbide often forms at grain boundaries in creep-resistant steels and plays a crucial role in creep resistance by blocking microstructural changes at elevated temperatures. Given that the dislocations and stacking faults (SFs) in carbides may affect their stability, the observation of SF formation in γ-M23 C6 using atomic-scale microscopy has implications for Cr-rich creep-resistant steels. Our analysis of SF energies (SFEs) derived from density functional theory calculations reveals that the SFEs are high, which suggests that the SF is not induced by external shear stress deformation but by lattice misfit between conjoined subgrains nucleated from the same austenite grain. Graphical abstract: (Color online) STEM observation of Cr-rich M23 C6 stacking fault (SF) and its nucleation mechanism between two γ-M23 C6 subgrains through two stages. First stage: two γ-M23 C6 subgrains—SG1 and SG2—initially grow toward one another from the same fcc matrix. Second stage: the subgrains collide, but do not exactly fit, creating a larger carbide particle with an SF. Image, graphical abstract